STEM-CP (Sains, Technology, Engineering Mathematics-Contextual Problem) Based Physics Module to Increase Student Literacy Skills at Vocational High School - M R Sari; Sutarto Sutarto; Sudarti Sudarti; Indrawati Indrawati; A S Budiarso (Pancaran Pendidikan, 2020)
Materials in physics learning at school are considered difficult to understand, especially in the concept of fluids. Students also frequently had misconceptions. Contextual issues are required to overcome this problem. STEM-CP (science, technology, engineering, mathematics-contextual problem) is seen to help students understand the concept of fluid through contextual issues. This study aimed to develop a module based on STEM-CP (Science, Technology, Engineering, Mathematics-Contextual Problem) in physics designed for a vocational school. This research used Quasi-Pretest-Posttest Experiment without a control class study obtained the data by using observation and testing of vocational schools in Jember. The study involved 35 students of SMK grade X. The data collected from the pretest and posttest using an open question correspond to the indicator of scientific literacy. The results showed an average of scientific literacy of students using STEM-CP based modules are in both categories in the cognitive domain and a very good product on the cognitive process.